A STUDY ON METAPHORS IN TI’I KA EMBU NUSI DISCOURSE IN RONGGA LANGUAGE - Erfiani, Yohanes Paulus Florianus (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This article is intended to investigate kinds of metaphors used in the discourse of Ti’i Ka Embu Nusi ‘Giving Food to Ancestors’ in Rongga Language (RL). It is also intended to investigate the cultural imagery expressed in the metaphors of Rongga language speakers (RLS). Many kinds of metaphors are used in the discourse of Ti’i Ka Embu Nusi in Rongga Language and Rongga Culture: structural metaphor, orientational metaphor and ontological metaphor. All metaphorical expressions belong to ontological metaphor. Nine of all the mataphors, beside belonging to ontological metaphor, are also belong to structural metaphor. Six of all the metaphors, beside belonging to ontological metaphor, also belong to orientational metaphor. It is also found the cultural imageryof the RLS was expressed in the metaphors appearing in the discourse of  Ti’i Ka Embu Nusi. (1) RLS believe that the ancestors are still alive even though they are not caught in five senses of the human being. Their eyes still can see their children living in the world, their ears still can hear their prayers, their noses still can smell foods, their tongues still can taste sweet, salty, or bitter of the drinks and the food, and their skins still can touch the human being. (2) RLS believe that the ancestors have power to protect or even to curse their living generation. (3) RLS desire good life condition for living in the world. This can be obtained by doing Ti’i Ka Embu Nusi. (4) RLS desire long life in the world. This can also be reached by doing Ti’i Ka Embu Nusi.